ANALISIS QOS DENGAN STANDARISASI TIPHON PADA LAYANAN TRIPLE PLAY MENGGUNAKAN GPON DI PT XYZ) - Aldiansyah; Boy Yuliadi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
This research aims to assess the Quality of Service (QoS) in Triple Play services utilizing Gigabit Passive Optical Network (GPON) technology at PT XYZ. The research focuses on implementing the TIPHON standard (Telecommunications and Internet Protocol Harmonization Over Networks) as a framework for evaluating service quality. The research methodology involves a survey of QoS parameters, including download speed, upload speed, and voice call quality. Additionally, the study includes an evaluation of GPON network performance based on the TIPHON standard. The results indicate that the implementation of the TIPHON standard enhances QoS in Triple Play services through GPON infrastructure at PT XYZ, with a significant improvement in QoS parameters. The analysis of GPON network performance, considering the TIPHON standard, aids in identifying areas for improvement to enhance efficiency and service quality.